2020
DOI: 10.4047/jap.2020.12.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface finishing treatments on the color stability of CAD/CAM materials

Abstract: The aim of this study was to evaluate the effect of different surface finishing processes on the color stabilities of lithium disilicate glass-ceramics, zirconia-reinforced lithium silicate ceramics, and resin nanoceramics after artificial ageing. MATERIALS AND METHODS. 216 samples were prepared from 3 different CAD/CAM materials (LAVA Ultimate, IPS e.max CAD, VITA Suprinity) with A1 HT color at a size of 14 × 12 mm and a thickness of 0.5 ± 0.05 mm. Color measurements of the samples were performed with a spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…10,13 Many authors have suggested that Lava Ultimate has the highest colour change compared to other ceramics after various surface treatments. 17,29 Similar results were found in this study as well.…”
Section: Discussionsupporting
confidence: 91%
“…10,13 Many authors have suggested that Lava Ultimate has the highest colour change compared to other ceramics after various surface treatments. 17,29 Similar results were found in this study as well.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, glazing was reported to lead to higher color stability and better mechanical properties. 27,29 However, different surface treatments may lead to different results. 25 Considering the novelty of ALDS, future studies investigating optical and mechanical properties of this material after different processes such as brushing, thermomechanical aging, and cyclic loading are needed to comprehensively understand its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A digital spectrophotometer (CM‐26d; Konica Minolta) 15 was used for color coordinate ( L *, which corresponds to lightness; a *, which corresponds to redness; b *, which corresponds to yellowness) 13,29,32 measurements. This spectrophotometer has a diffused illumination integrating sphere system (8° viewing) and two specular component modes (specular component included and excluded).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Again, no cementation was performed, which may be the reason for differences from the present study results in terms of perceptibility. Ozen et al 29 studied the color stability of CAD‐CAM materials after cementation with a translucent shade resin cement and thermocycling. The effect of translucent cement applied on the color of 0.5 mm ZLS specimens was similar to the effect of the cements recorded after cementation in the present study.…”
Section: Discussionmentioning
confidence: 99%